Is Greater Social Support from Parents and Friends Related to Higher Physical Activity Levels among Adolescents? - Edina Maria de Camargo; Cristiane Galvão da Costa; Thiago Silva Piola; Eliane Denise Araújo Bacil; José Francisco López-Gil; Wagner de Campos (MDPI AG, 2023)
Increasing physical activity levels during adolescence have been put on the agenda by several researchers. This study verified the association between social support from parents and friends and different amounts of moderate-to-vigorous physical activity (MVPA) among adolescents in public school. The present study had a cross-sectional design and included a representative sample of 1984 adolescents (aged 15-17). The ASAFA (Apoio Social para prática de Atividade Física para Adolescentes) scale and the QAFA (Questionário de Atividade Física para Adolescentes) were used to determine social support and physical activity, respectively. For statistical analysis, a conceptual model for structured equations and weighted least squares mean and variance adjusted were applied. Social support from parents increased the odds of engaging in 180 min/week of MVPA by 46.7%, 47.8% for 300 min/week, and 45.5% for 420 min/week. Social support from friends showed similar relations trends: 23.8% for 180 min/week, 23.6% for 300 min/week, and 21.2% for 420 min/week. Social support from parents and friends increased the probability of adolescents reaching the amounts of physical activity investigated. The results indicate that greater social support (from parents and friends) was associated with a higher level of MVPA in Brazilian adolescents.